Application of genetic screening in families with hereditary medullary thyroid carcinoma - Frank-Raue, Karin; Höppner, Wolfgang; Buhr, Heinz J.; Herfarth, Christian; Ziegler, Reinhard; Raue, Friedhelm (Experimental and clinical endocrinology & diabetes, 1996)
Thieme E-Books & E-Journals